Preoperative alcohol consumption, intraoperative bleeding and postsurgical pain may increase the risk of postoperative delirium in patients undergoing radical retropubic prostatectomy - Ladjević, Nikola; Knežević, Nebojša Nick; Magdelinić, Andjela; Likić Ladjević, Ivana; Durutović, Otaš; Stamenković, Dušica; Jovanović, Vesna; Ladjević, Nebojša (Vojnosanitetski pregled, 2021)
Background/Aim. The incidence of postoperative delirium (POD) after non-cardiac surgery is a problem not often recognized by many anesthesiologists. The objective of our study was to detect POD and its possible cause, in patients undergoing radical retropubic prostatectomy (RRP) under general anesthesia. Methods. After Ethical Committee approval, we enrolled 80 patients, ASA (the American Society of Anestesiology) status II, scheduled to undergo RRP under general anesthesia, in a prospective study. All patients completed MMSE tests (the Folstein Mini Mental State Exam) the evening before, and 48 hours after the surgery. Assessment for the presence and severity of delirium was performed using CAM (the Confusion Assessment Method), and an assessment of the degree of agitation and sedation using RASS (the Richmond Agitation and Sedation Scale). Results. The average preoperative MMSE score (28.59 ± 1.04) significantly decreased following the surgery (27.74 ± 1.52) (p
Keywords: delirium; postoperative complications; alcohol consumption; bleeding; postoperative pain; risk factors; prostatectomy